Ent-labdane and beyerane diterpenes from Erythroxylum betulaceum Mart - Ribeiro, Erika M. de O.; David, Juceni P.; David, Jorge M.; Guedes, Maria L.S.; Lopes, Lucia M.X. [UNESP]; Kršková, Zuzana; Dušek, Jaroslav (Elsevier, 2013)
•Diterpenes were isolated from wood of Erythroxylum betulaceum Mart.•Two ent-labdanes and one ent-beyrane diterpenes were isolated.•Diterpenes together tropanic alkaloid and may be useful as a chemotaxonomic markers of Erythroxylum. © 2013 Elsevier Ltd.
Keywords: Beyerane diterpene; Ent-labdane diterpenes; Erythroxylaceae; Erythroxylum betulaceum; alkaloid; chemotaxonomy; deciduous tree; genetic marker; terpene